PENGARUH KOMPENSASI DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI (Studi Kasus pada Dinas Kelautan dan Perikanan KabupatenTulungagung) - Suprihatin Suprihatin (Universitas Islam Kadiri, 2019)
This research is an ex-post facto funds sosiatif causal aims to determine: (1) the impact of compensation on employee performance, (2) the effect of work motivation on employee performance, and (3) the effect of Compensation and Working Motivation together-together on Employee Performance, The study population was all employees of the Department of Marine and Fisheries District Court Tulung totaling 62 pegawai.Sampel used in this study is a population which total 62 employees in the sample, so-called research instrument populasi. Uji try to do in the Office of Marine and Fisheries District Tulungagung.Uji validity of using correcteditem total correlation, while the reliability test using cronba chalpha.Uji classical assumptions include linearity test, multicollinearity test, and test heteroskedastisitas.Uji hypothesis in this study using simple regression analysis and multiple regression analysis. The results of this study indicate that: (1) There is a positive and significant impact on Employee Performance Compensation in the Department of Marine and Fisheries in Tulungagung. 2) There is a positive and significant impact work motivation on employee performance 3) There is a positive and significant impact Compensation and Motivation Work together on Employee Performance